ANALISIS PEMASARAN BAWANG MERAH (Allium ascalonicum) DI DESA SUNGAI GERINGGING KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - Priyana, Rista Hardi; Tety, Ermi; ', Eliza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objectives of this research were to 1). Know the function, channel and marketing agencies onion. 2). Analyze costs, margins, profibality, efficiency and the share of the farmer. 3). Knowing the marketing problems of onion at Sungai Geringging Kampar Kiri districk in Kampar regency. This study usues survey, sampling was done by purposive sampling of 30 samples onion farmers at Sungai Geringging Kampar Kiri districk in Kampar regency. Taking sample of trader used snowball sampling by following marketing channel. The outcome of this research indicated the function-function of onion marketing at Sungai Geringging such as buy function, sale function, clean function, storage function, transportation function, standardization function, risk tackling function, market information function, financial capital function.There are 2 marketing channel 1). Farmer–trader of collector–trade of retailer–consumen. 2). Farmer–trader of collector–bigtrader–trader of retailer–consumen. The total cost of marketing collector is Rp 416,67/kg, retailers channel I is Rp 153,02/kg. Marketing costs of bigtrader channel II is Rp 275/kg and retailers channel II is Rp 176,03/kg. Marketing margins of channel I is Rp 3.166,67/kg and channel II is Rp 4.100/kg. Total profit of channel I is Rp 2.596,98/kg and channel II is Rp 3.232,30/kg. The efficiency of channel I is 2,46% and channel II is 3,60%. Problems faced by farmer is the weather and the price, while the problems faced by traders is the price. Keywords: Marketing, Function, Channel, Margins, Eficiency.